Nursing interventions for self-care in older adults with prostate cancer at a local hospital of Chiclayo, 2025 - Morales Diaz, Florencia Sarait (2025)
Nursing interventions for self-care in older adults with prostate cancer promote a more effective recovery, increasing their overall well-being and granting them independence. Objective: To describe and analyze nursing interventions for self-care in older adults with prostate cancer at a local hospital in Chiclayo, 2025. Materials and methods: A qualitative approach with a descriptive design was developed. The population consisted of 17 nursing professionals working in the oncology unit, including those with at least 6 months of experience in the service and willing to participate in the research. The sample consisted of 12 nursing professionals. The sampling was non-probabilistic for convenience, determined by saturation and redundancy. A semi-structured interview guide validated by experts was used to collect data, and a pilot test was conducted. The analysis was performed using the thematic analysis technique. The project was governed by Sgreccia's bioethical criteria, ensuring scientific rigor. Results: Three categories emerged: Nursing educational actions to strengthen self-care, Clinical and nursing care to promote therapeutic self-care, Relational support to strengthen care. Conclusion: Nursing interventions in self-care not only promote physical and emotional recovery, but also strengthen patient confidence and family participation, improving their quality of life and reducing complications.